Syntheses, Structures, and Magnetic Properties of Cobalt(II) Complexes with Pyridyl‐substituted Nitroxide Radicals. Issue 3 (25th November 2014) - Wang, Xiaoling; Bao, Xia; Wei, Yijun; Wang, Fengwu; Wen, Guilin
Abstract: Two cobalt(II) radical complexes: [Co(NIT4‐py)2 (PNB)2 ] (1 ) and [Co(im4‐py)2 (PMB)2 (H2 O)2 ] (2 ) [NIT4‐py = 2‐(4′‐pyridyl)‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl 3‐oxide, im4‐py = 2‐(4′‐pyridyl)‐4, 4, 5, 5‐tetramethylimidazole‐1‐oxyl, PNB = p ‐nitrobenzoic anion, PMB = p ‐methylbenzoic anion] were synthesized and characterized. X‐ray diffraction analysis shows that complex1 is four coordinated with tetrahedral arrangement, where the Co II ion is located in the central site of the tetrahedron, two radicals and two PNB ligands are trans ‐coordinated to the Co II ion. Complex2 exhibits a six coordinated distorted octahedron, in which two im4‐py radicals, two PMB ligands, and two solvent molecules act as terminal ligands. The magnetic behaviors of complexes1 and2 were investigated. Complex1 shows ferromagnetic interactions between the Co II ion and the NIT4‐py radical, whereas antiferromagnetic coupling dominates between the im4‐py radical and the Co II ion in complex2 . The magnetic properties can be explained by the structures and a magnetic exchange mechanism. Abstract :